IBD-related disability among patients with ulcerative colitis in China: a cross-sectional study - Mengyuan Zhang; Xiaojuan Liu; Shichen Min; Hong Shen; Lei Zhu (Therapeutic Advances in Gastroenterology)
Background: Ulcerative colitis (UC) is a chronic inflammatory disorder that can lead to physical, psychological, and social disabilities among patients. Objectives: To evaluate the disability level in a cross-sectional study of Chinese patients with UC and identify factors associated with disability. Design: This was a cross-sectional study. Methods: Between April 2022 and March 2023, UC patients from the Affiliated Hospital of Nanjing University of Chinese Medicine responded to questionnaires including the Inflammatory Bowel Disease Disability Index (IBD-DI), Fatigue Severity Scale, Patient Health Questionnaire-9, and Generalized Anxiety Disorder-7. In addition, demographic characteristics and clinical data of the patients were collected. Associated factors were identified by univariate and multivariate logistic regression analyses. Results: A total of 345 patients completed the questionnaires. The median (interquartile range) IBD-DI score was 16.2 (9.6–26.5), and the overall prevalence of disability was 39.7%. IBD-DI correlated with Mayo score, fatigue, anxiety, depression, hemoglobin (HGB), albumin (ALB), and erythrocyte sedimentation rate (ESR). Furthermore, the self-reported disability (IBD-DI > 20) was associated with lower BMI, active UC, disease severity of moderate and severe, disease location of left-sided UC (E2), using corticosteroids or biologics for treatment, Mayo score, fatigue, depression, anxiety, HGB, ALB, complement 3 (C3), and ESR. Notably, lower BMI, higher Mayo score, fatigue, and depression were identified as independent risk factors of disability in UC patients. Conclusion: This study revealed a significant level of disability among the Chinese UC population. Several clinical factors were identified to affect the level of disability, notably the risk factors including BMI, disease severity, fatigue, and depression.